Management of patients who opt for radical prostatectomy during the coronavirus disease 2019 (COVID‐19) pandemic: an international accelerated consensus statement. (10th March 2021) - Tandogdu, Zafer; Collins, Justin; Shaw, Greg; Rohn, Jennifer; Koves, Bela; Sachdeva, Ashwin; Ghazi, Ahmed; Haese, Alexander; Mottrie, Alex; Kumar, Anup; Sivaraman, Ananthakrishnan; Tewari, Ashutosh; et al.
Abstract : Objective: Coronavirus disease‐19 (COVID‐19) pandemic caused delays in definitive treatment of patients with prostate cancer. Beyond the immediate delay a backlog for future patients is expected. The objective of this work is to develop guidance on criteria for prioritisation of surgery and reconfiguring management pathways for patients with non‐metastatic prostate cancer who opt for surgical treatment. A second aim was to identify the infection prevention and control (IPC) measures to achieve a low likelihood of coronavirus disease 2019 (COVID‐19) hazard if radical prostatectomy (RP) was to be carried out during the outbreak and whilst the disease is endemic. Methods: We conducted an accelerated consensus process and systematic review of the evidence on COVID‐19 and reviewed international guidance on prostate cancer. These were presented to an international prostate cancer expert panel ( n  = 34) through an online meeting. The consensus process underwent three rounds of survey in total. Additions to the second‐ and third‐round surveys were formulated based on the answers and comments from the previous rounds. The Consensus opinion was defined as ≥80% agreement and this was used to reconfigure the prostate cancer pathways. Results: Evidence on the delayed management of patients with prostate cancer is scarce. There was 100% agreement that prostate cancer pathways should be reconfigured and measures developed to prevent nosocomial COVID‐19 for patients treated surgically. Consensus was reached on prioritisation criteria of patients for surgery and management pathways for those who have delayed treatment. IPC measures to achieve a low likelihood of nosocomial COVID‐19 were coined as 'COVID‐19 cold' sites. Conclusion: Reconfiguring management pathways for patients with prostate cancer is recommended if significant delay (>3–6 months) in surgical management is unavoidable. The mapped pathways provide guidance for such patients. The IPC processes proposed provide a framework for providing RP within an environment with low COVID‐19 risk during the outbreak or when the disease remains endemic. The broader concepts could be adapted to other indications beyond prostate cancer surgery.